2020
DOI: 10.1038/s41589-020-0495-z
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical mitotic exit induced by a small molecule inhibitor of APC/CCdc20

Abstract: The Anaphase Promoting Complex/Cyclosome (APC/C) is a ubiquitin ligase that initiates anaphase and mitotic exit. The APC/C is activated by Cdc20 and inhibited by the mitotic checkpoint complex (MCC), which delays mitotic exit when the spindle assembly checkpoint (SAC) is activated. We previously identified apcin as a small molecule ligand of Cdc20 that inhibits APC/C Cdc20 and prolongs mitosis. Here we find that apcin paradoxically shortens mitosis when SAC activity is high. These opposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…[24][25][26] CDC20 is a vital conserved cell cycle regulator that modulates ubiquitin ligase activity of the APC/C complex at the moment of the metaphase-anaphase transition in mitosis and degrades the substrates of APC/C CDC20 including securin and cyclin A. 27,28 Previous researches have revealed that CDC20 suppressed apoptosis while accelerated the proliferation and invasion of osteosarcoma cells. 29,30 Cyclin A2, as part of the substrates of APC/C CDC20 , is tightly linked with the process of sister chromatid segregation.…”
Section: Dovepressmentioning
confidence: 99%
“…[24][25][26] CDC20 is a vital conserved cell cycle regulator that modulates ubiquitin ligase activity of the APC/C complex at the moment of the metaphase-anaphase transition in mitosis and degrades the substrates of APC/C CDC20 including securin and cyclin A. 27,28 Previous researches have revealed that CDC20 suppressed apoptosis while accelerated the proliferation and invasion of osteosarcoma cells. 29,30 Cyclin A2, as part of the substrates of APC/C CDC20 , is tightly linked with the process of sister chromatid segregation.…”
Section: Dovepressmentioning
confidence: 99%
“…Second, it would be necessary to perform an experiment to show, for example, that the same over expressed peptide derived from Cdc20 from between the ‘C-box’ and the ‘Mad2-binding motif’ or ‘KILR motif’ does not affect MCC function by observing under the light microscope if any cells escape from a benomyl arrest when the peptide is expressed. This experiment is required because of the unexpected result displayed by apcin, where it displayed great promise as an APC/C Cdc20 -specific inhibitor, but, unfortunately, also disrupts the function of the MCC, thus allowing cancer cells to still execute ‘mitotic slippage’ by entering anaphase, even in the presence of a mitotic poison [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the current only known essential function of the APC/C Cdc20 form of the holoenzyme in humans is the promotion of somatic cell mitotic cell division, or it is also likely to be involved in the promotion of the metaphase II–anaphase II advance during meiosis II in gametogenesis, as in mice [ 23 ]. Surprisingly, even the most promising APC/C Cdc20 inhibitor molecule apcin gave an unexpected result, namely, in the absence of mitotic poisons, it induced the expected cell cycle arrest at metaphase, but in the presence of mitotic poisons, which would be the expected conditions in cancer cells in individuals undergoing chemotherapy, apcin induced ‘mitotic slippage’, rather than preventing it, by not only decreasing APC/C Cdc20 activity, but also by blocking mitotic checkpoint MCC function, the opposite of the desired result [ 24 ]. Thus, the goal to identify a specific APC/C Cdc20 inhibitor that can extend a mitotic poison induced spindle checkpoint arrest remains unfulfilled.…”
Section: Introductionmentioning
confidence: 99%
“…CDC20, which was key to chromosome segregation and mitosis exit, plays an important role in cell cycle progressing [43]. It can activate a ligase, the anaphase-promoting complex/cyclosome (APC/C), which starts the anaphase and mitotic exit [44]. Cheng et al shown that overexpression of CDC20 promotes the metastasizing of breast cancer [45].…”
Section: Discussionmentioning
confidence: 99%